A process and criteria for the evaluation of software frameworks in the domain of computer assisted surgery. - Bohn S; Korb W; Burgert O; Bohn, Stefan; Korb, Werner; Burgert, Oliver (Medical & Biological Engineering & Computing, 2008)
Software application frameworks provide a modular and reusable context for the development of custom applications, e.g. in the domain of medical image processing and computer assisted surgery (CAS). The utilization of an appropriate software framework can strongly reduce time and costs for software design, implementation, and validation. However, the decision to apply a particular framework poses many risks that can have an impact on the success of the overall software project. There is a need for a software framework evaluation methodology that guides the selection process in an objective, impartial, and repeatable manner. This work defines an evaluation process for the selection of software application frameworks out of a group of candidates that fit best to defined requirements necessary for the development of CAS applications.